Light-dependent cytolysis in the allelopathic interaction between picoplanktic and filamentous cyanobacteria - Barreiro Felpeto A. (2018)
Allelopathic compounds produced by cyanobacteria may play important roles in the dynamics of several biological systems. The main goal of this work was to investigate reciprocal allelopathic effects between species of two relevant groups of marine cyanobacteria: The picocyanobacterium Synechococcus sp. and the filamentous species Nodularia spumigena. Our experimental design consisted of cell-free filtrates and co-cultures. We demonstrated that Synechococcus sp. had a strong inhibitory effect on N. spumigena, and surprisingly, there was no reciprocal effect from the filamentous cyanobacteria. We detected this effect both in co-cultures and cell-free filtrate bioassays. These effects depended on light conditions in the culture of the allelopathic species. This allelopathic effect against N. spumigena triggered physiological responses leading to reduced chlorophyll a (Chl a) and carotenoid (Car) content, cell shape distortions and, often, cell lysis. Surprisingly, no evidence was found of allelopathic effects of our strain of N. spumigena (a well-known allelopathic species) against Synechococcus sp. These results support the fact that allelopathic interactions between Synechococcus sp. and N. spumigena may be a factor influencing the formation of massive bloom of the former organisms in many aquatic ecosystems, like the Baltic Sea, where the two species constitute a relevant fraction of phytoplankton biomass. © The Author(s) 2018. Published by Oxford University Press. All rights reserved. For permissions, please e-mail: journals.permissions@oup.com.